HIGH-SPIN COORDINATION COMPOUNDS OF 3D-METALS - PERSPECTIVE MOLECULAR MAGNETS (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
The phenomena of ferromagnetism as well as ways of chemical designing of magnetoactive molecules are considered for thе cases of polynuclear structures with high-spin 3d-metals atoms of the VII and VIII groups.
Keywords: -